Utilisation of new media in communicating insecurity in Southeast Nigeria - Jumbo , Cynthia N.; Asemah, Ezekiel S.; Anyanwu, BJC; Onyebuhi, Alexander Chima; Etumnu, Emeka Williams; Anyi, Oba Sunday Aikuirawo (Universitas Ahmad Dahlan, 2023)
This paper aims to describe how in recent times, the issue of insecurity in the southeast of Nigeria is alarming. People are no longer safe as they have become targets for the perpetrators of insecurity within the region. In all of these cases, people must be fully aware of the level of insecurity in a specific location in order to determine the next course of action. In order to achieve this, this study examined the use of new media to communicate insecurity in Southeast Nigeria. The study was founded on the premise of technological determinism. In this research, a survey research approach was used. Using the Wimmer and Dominick sample size calculator, a sample of 384 was generated from the study's population of 22,012,828. A questionnaire was utilised as a data collection tool. Meanwhile, the multistage sampling procedure was used. Data was analysed with the use of descriptive statistics and pie chart. The finding showed that 51.0% of respondents had been exposed to insecurity messages via new media to a very large extent. It was also revealed that on an average of 74.8% (N=367), new media has been used in communicating insecurity among residents in southeastern Nigeria to a very large extent. It was recommended that new media users should be sensitized on the need to use the platform appropriately or with a sense of responsibility instead of using it to fuel more security problems within the southeastern region of Nigeria.